Study Protocol for Assessment of the Feasibility of an Intraoperative Localization Technique Using Augmented Reality in Breast‐Conserving Surgery for Non‐Palpable Cancer Lesions: A Feasibility Study - Alexia Giro; Judith Passildas; Emilie Thivat; Ioana Molnar; Céleste Pinard; Wissam Marraoui; Adrien Bartoli; Rasoul Sharifian; Nicolas Bourdel; Catherine Abrial; Christophe Pomel; Xavier Durando; et al. (Health Science Reports, 2026)
ABSTRACT Background and Aims Localizing non‐palpable cancerous lesions of breast‐conserving surgery is a major challenge. Augmented reality (AR) and 3D imaging are emerging tools for surgical guidance. This study evaluates the feasibility of a noninvasive intraoperative localization technique using AR. Methods This prospective, interventional, single‐center proof‐of‐concept study investigates AR‐assisted localization of non‐palpable breast lesions. Secondary objectives include surgical time assessment, breast phantom development, and fusion feasibility between supine 3D breast MRI images and post‐MRI ultrasound with target lesion detection. The study includes an additional MRI in supine position and intraoperative 3D images of the patient's chest captured with a 3D camera. A 3D reconstruction of the patient's chest and lesions will be performed from the MRI images, called the preoperative 3D model. A total of five patients eligible for assessment are expected. Conclusion The challenge of this study is the development of a noninvasive intraoperative localization technique using AR from preoperative images in breast‐conserving surgery. If this study is successful, a randomized trial will be designed to compare the accuracy of the intraoperative localization technique using AR with that of the gold standard intraoperative breast ultrasound.